1973
DOI: 10.1680/macr.1973.25.83.73
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rate of loading upon the static and fatigue strengths of plain concrete in compression

Abstract: Synopsis The paper describes an experimental investigation into the effect of the rate of application of steadily increasing loads upon the static strength and of fluctuating loads upon the fatigue strength of plain concretes in compression. Concretes made with gravel, limestone or Lytag aggregate were tested. Increasing the rate of application of load was found, in general, to enhance the static strength andfatigue strength of all three types of concrete. The increase in static strength was found to be great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(62 citation statements)
references
References 0 publications
1
43
0
1
Order By: Relevance
“…6 and 7 against the collected existing experimental results [6,8,19,25,41,45,49]. The main trend of the increase of strength under fast loading is well reproduced.…”
Section: Uniaxial Dynamic Behaviorssupporting
confidence: 58%
“…6 and 7 against the collected existing experimental results [6,8,19,25,41,45,49]. The main trend of the increase of strength under fast loading is well reproduced.…”
Section: Uniaxial Dynamic Behaviorssupporting
confidence: 58%
“…In addition, it was reported that the strain-rate sensitivity of concrete varied with aggregate quality. Sparks and Menzies [19] found that the increase in strength was greater in concrete with a relatively weak and soft aggregate than that in concrete with relatively strong aggregate. Since the recycled aggregates are normally weaker than the natural aggregates [1,2], it is expected that the strain-rate sensitivity of RAC is different from that of NAC.…”
Section: Introductionmentioning
confidence: 98%
“…At present, it is accepted that frequency values between 1 and 15 Hz hardly have any influence on fatigue life, provided that the maximum stress level is not over 75% of the compressive strength [22][23][24][25][26]. Noteworthy is the research developed by Zhang and Wu [27], which proposed, for the first time, an S-N curve as a function of the frequency of the cyclic load.…”
Section: Load Frequencymentioning
confidence: 99%
“…Numerous investigative works have demonstrated that there is a direct relation between the secondary creep rate and the fatigue life. The secondary creep rate depends on the loading frequency and the maximum strain level [23,28,29,37].…”
Section: Variation Of Deformation With the Number Of Cyclesmentioning
confidence: 99%